Social media analytics: tools, techniques and present day practices. (29th January 2022) - Nanda, Pooja; Kumar, Vikas
As a result of the availability of web-based application programming interfaces (APIs) for social networking sites, the study of social media has become a major research and business practice. This environment is evolving rapidly due to market demands and enormous applications. This paper presents a comprehensive review of leading social media analytics tools available for various social networking platforms. A comparative analysis has been carried out for the free and subscription based tools to judge their suitability for specific organisation. Various challenges are faced by businesses in adopting social media analytical tools to support the knowledge based business strategies. Correspondingly, the present day corporate challenges from the perspective of social media analytics in its adoption for corporate decisions have been outlined. This work will be very much useful for organisations in identifying the various tools available in the market, which may help them take knowledge based strategic decisions.